Islamic Religious Education Learning Based on Spiritual Intelligence in Developing Students' Morals at SMKN 1 Sorong City - Haerunnisa Haerunnisa; Indria Nur; Rusyaid Rusyaid; Muhammad Rusdi Rasyid; Fatma Sari (Journal of Educational Sciences, 2026)
Islamic Religious Education (PAI) learning in vocational schools is often cognitively oriented, thus failing to fully develop students' moral awareness. This study aims to analyze the role of spiritual intelligence-based Islamic Religious Education (PAI) learning in enhancing students' moral awareness at SMK Negeri 1 Sorong City. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with teachers and students, and documentation. Data were then analyzed using data reduction, data presentation, and thematic conclusion drawing techniques. The results indicate that the integration of spiritual intelligence values into Islamic Religious Education (PAI) learning is achieved through reflection on meaning, value dialogue, habituation of worship, and teacher role models, thus encouraging the internalization of moral values more contextually in students' lives. Learning not only produces conceptual religious understanding but also fosters self-awareness, responsibility, and concrete religious behavior. These findings confirm that a spiritual intelligence-based approach contributes to transforming Islamic Religious Education (PAI) learning from merely transferring knowledge to developing students' moral character.